The Modeling of the Artistic Effect of Syntactic Means for Character Depiction in Poetry - HAMBARDZUMYAN, HAYK (Bulletin of Yerevan University B: Philology, 2021)
The goal of the present article is to uncover the literary effect of syntactic means of character depiction in poetry. A research is conducted among expressive syntactic means aiming to find out their intrinsic potential to serve the mentally strenuous process of depicting characters in works of poetry. The investigation elicits the effects that the abovementioned means have on shaping the main traits and ideological vectors of characters. The results of the research are epitomized by a model designed to be employed as a tool for analyzing characters in all sorts of poetic works.
Keywords: character, depiction, expressive syntax, effect, locution, devices, poetic syntax, poetry, model